The Epidemiology of Neurological Complications in Adults With Sickle Cell Disease: A Retrospective Cohort Study - Maduakor, Chinedu; Alakbarzade, Vafa; Sammaraiee, Yezen; Vakrinou, Angeliki; Corobana, Alina; Sikorska, Julia; Rhodes, Elizabeth; Pereira, Anthony C. (Frontiers in Neurology, 2021)
Introduction: Risk factors for neurological complications in sickle cell disease differ in the adult and pediatric population. Here, we focused on neurological complications in adults with sickle cell disease. Methods: Patients were selected using audit data from the St George’s Hospital Red Cell Database. Genotyping, demographics, clinical data and investigation findings were collected. Results: A total of 303 patients were enrolled: HbSS genotype 56%, HbSC genotype 35%, HbSβ thalassemia genotype 9%; mean age was 38.8yrs (±13.5 SD) with 46% males. The most common neurological complication was cerebrovascular disease (n=37, 12%) including those with ischemic stroke (10%), cerebral vasculopathy (3%) and intracranial hemorrhage (1%). Ischemic stroke was common among the HbSS genotype compared to other genotypes (8% vs 1.6%, p=0.001). Comparing sickle cell disease patients who had suffered stroke to those who had not, there was a higher proportion of intracranial vasculopathy (p=0.001, in particular Moyamoya) and cognitive dysfunction (p<0.0001). Conclusion: Our cohort supports previous reports that the most common neurological complication in the adult sickle cell patients is cerebrovascular disease. Strategies to prevent cerebral vasculopathy and cognitive impairment should be explored.